Optimization of Drying Process for Squid-Laver Snack by a Combined Method of Fuzzy Synthetic and Response Surface Methodology. (19th December 2017) - Zhao, Chang-Cheng; Jiang, Gui-Hun; Eun, Jong-Bang
Abstract : The aim of this study was to investigate the effects of drying temperature (50–70°C) and drying time (3–5 h) on the physical properties and quality of squid-laver snack (SLS) using response surface methodology combined with a synthetic evaluation method to optimize the drying process conditions. Moisture content, water activity, color (L ⁎, a ⁎, b ⁎ ), shear force, and overall acceptability were evaluated as responses. Increased drying times and higher temperatures significantly reduced the moisture content and water activity of SLS from 9.07% to 4.76% and 0.136 to 0.056, respectively (p < 0.05 ). There was no significant difference in the L ⁎ and a ⁎ values under different drying conditions. The quadratic effect of temperature and time was observed for the b ⁎ value and overall acceptability of SLS. For shear force, a quadratic and interaction term for drying temperature and time on shear force was observed. In conclusion, the recommended optimal hot air-drying conditions for SLS are temperature and time of 70°C and 3 h, respectively.